Financial Management in the Implementation of School Well-Being at SMP Negeri 2 Pemalang - Urip Suwarniti; Endang Wuryandini; Muhtarom Muhtarom (FKIP - Universitas Riau, 2026)
This study describes the school financial management program through the stages of planning, implementation, monitoring and evaluation, and optimization strategies to support the school well-being program at SMP Negeri 2 Pemalang. A descriptive qualitative approach was used in this study, with the principal, vice principal, treasurer, teachers, and school committee members as subjects. Data were obtained through in-depth interviews, observation questionnaire, and documentation. Data were then analyzed through the stages of reduction, presentation, and conclusion drawing. The results indicate that the financial planning stage was carried out systematically, based on data, and involved all parties and community elements. The financial implementation stage was conducted transparently and accountably using digital technology. The monitoring and evaluation stage used a continuous and tiered cycle encompassing formative, summative, and reflective approaches. Furthermore, the financial optimization strategy was implemented through efficient fund allocation and external partnerships to maximize priority programs. Further research is essential to explore this further and obtain more measurable results.